Microcredit and insertion tool financial and socio among immigrants (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The purpose of this paper is to support the hypothesis that microcredits are avalid tool in the social and financial inclusion processes of immigrants into a developed country such as Spain. In this manner, there is a mutual benefit for both receiving and sending countries. The integration of a working age immigrant population with a strong entrepreneurial spirit, through the access to microcredit programmes,will facilitate their self employment and inclusion into a stable labour market. Hence reducing the ratio of workers to retirees. The outflow of workers will alsogenerate remittances in favour of the sending countries.
Keywords: Microcredits; Immigrants; Social and Financial Exclusion and Inclusion; Self-employment; Ratio of workers to retirees and Remittances.